TEKNOLOGI, PERDAGANGAN INTERNASIONAL DAN PERTUMBUHAN EKONOMI: SUATU KAJIAN TEORI EKONOMI KLASIK KE PERDAGANGAN INTERNASIONAL MODERN - Sidik Budiono (Fakultas Bisnis Universitas Kristen Duta Wacana, 2011)
ABSTRACT There are 3 phenomens of most economic which undivided that openess and international trade and economic growth. Openess is the first frame for most country to do consolidation for its capability and weakness. International trade have able support high economic growth signify-cantly. This paper would like to inform us about development of international economic from Classical Economic era to Modern International Economic (integra-tion of endogenous growth and trade). The analyzis is not only compa-rative static approach but also intertemporal approach. Scientificly the country’s advantage of modern international trade is not only ana-lyzed for technology and specialization but also countries’s factor share. Generally, all countries tend to the long term equilibrium in the balance growth path. Therefore, each country and rest of the world will able to meet welfare economy not only individually but also international. Keywords: Technology, International Trade, Economic Growth